Regulation of COX Assembly and Function by Twin CX(9)C Proteins—Implications for Human Disease - Gladyck, Stephanie (Cells, 2021)
Oxidative phosphorylation is a tightly regulated process in mammals that takes place in and across the inner mitochondrial membrane and consists of the electron transport chain and ATP synthase. Complex IV, or cytochrome c oxidase (COX), is the terminal enzyme of the electron transport chain, responsible for accepting electrons from cytochrome c, pumping protons to contribute to the gradient utilized by ATP synthase to produce ATP, and reducing oxygen to water. As such, COX is tightly regulated through numerous mechanisms including protein–protein interactions. The twin CX(9)C family of proteins has recently been shown to be involved in COX regulation by assisting with complex assembly, biogenesis, and activity. The twin CX(9)C motif allows for the import of these proteins into the intermembrane space of the mitochondria using the redox import machinery of Mia40/CHCHD4. Studies have shown that knockdown of the proteins discussed in this review results in decreased or completely deficient aerobic respiration in experimental models ranging from yeast to human cells, as the proteins are conserved across species. This article highlights and discusses the importance of COX regulation by twin CX(9)C proteins in the mitochondria via COX assembly and control of its activity through protein–protein interactions, which is further modulated by cell signaling pathways. Interestingly, select members of the CX(9)C protein family, including MNRR1 and CHCHD10, show a novel feature in that they not only localize to the mitochondria but also to the nucleus, where they mediate oxygen- and stress-induced transcriptional regulation, opening a new view of mitochondrial-nuclear crosstalk and its involvement in human disease.